Terapi Sel Punca Mesenkimal pada Diabetes Melitus Tipe 2: Tinjauan Sistematis terhadap Outcome HbA1c - M.Nazhim Alhani; Esa Zahirah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study evaluates the effectiveness of Mesenchymal Stem Cell (MSC) therapy in lowering HbA1c levels among patients with Type 2 Diabetes Mellitus (T2DM). A systematic review was conducted using PubMed, ScienceDirect, and Google Scholar with the keywords “Type 2 Diabetes Mellitus,” “Mesenchymal Stem Cell,” and “HbA1c,” covering studies published between 2022–2025. Four primary studies met the inclusion criteria, involving 438 patients treated with MSCs from various sources. Most studies reported significant HbA1c reduction after MSC infusion, particularly with UC-MSC therapy, which showed a decrease of over 1% within 48 weeks. The effect was more pronounced in patients with a shorter diabetes duration (≤10 years) and lower BMI (<23 kg/m²). The conclusion is that MSC therapy has been proven to improve glycemic control with a favorable safety profile. However, further large-scale and long-term studies are needed to confirm its effectiveness and determine the optimal clinical application. Keywords: Type 2 Diabetes Mellitus, HbA1c, Mesenchymal Stem Cell